Phenotypic methods and commercial systems for the discrimination between C-albicans and C-dubliniensis - Campanha, N. H.; Neppelenbroek, K. H.; Spolidório, Denise Madalena Palomari [UNESP]; Spolidório, Luis Carlos [UNESP]; Pavarina, Ana Claudia [UNESP] (Blackwell Publishing, 2005)
Candida dubliniensis is a recently described Candida species associated with oral candidosis that exhibits a high degree of phenotypic similarity to Candida albicans. However, these species show differences in levels of resistance to antimycotic agents and ability to cause infections. Therefore, accurate clinical identification of C. dubliniensis and C. albicans species is important in order to treat oral candidal infections. Phenotypic identification methods are easy-to-use procedures for routine discrimination of oral isolates in the clinical microbiology laboratory. However, C. dubliniensis may be so far underreported in clinical samples because most currently used identification methods fail to recognize this yeast. Phenotypic methods depend on growth temperature, carbon source assimilation, chlamydospore and hyphal growth production, positive or negative growth on special media and intracellular enzyme production, among others. In this review, some phenotypic methods are presented with a special emphasis on the discrimination of C. dubliniensis and C. albicans.
Keywords: candidiasis, oral; Candida; Candida albicans; pathology, oral; isolation and purification; Candida dubliniensis